Prevention Efforts Against the Use of Mixed Alcoholic Beverages in the Cicalengka Area, Bandung Regency - Sari, Wiwit Juliana; Kurniati, Yeti (Formosa Journal of Sustainable Research, 2024)
Mixed liquor has caused many deaths in Cicalengka, Bandung Regency, thus attracting the attention of the Indonesian people. This study uses a juridical-social method as well as library and field data collection techniques. Several preventive efforts have been carried out by one of the authorized law enforcement agencies, namely the Cicalengka Police. Preventive measures taken include preventive efforts in the form of routine socialization and education of the community to avoid consumption and trade of mixed liquor and routine raids, and repressive efforts in the form of confiscation of evidence and follow-up to incidents related to the use of mixed liquor. There are many obstacles that hinder efforts to overcome the use of mixed liquor in Cicalengka. First, consuming mixed liquor has become a culture of the community in the Cicalengka area that normalizes the consumption of mixed liquor. Second, public education and understanding of mixed liquor are still very low. Many people assume that legal and mixed liquor have the same composition and side effects. The third obstacle is the inconsistency between the laws and regulations regarding mixed alcoholic beverages and the inconsistent attitude of the law makers in regulating these laws